An International Educational Literacy: Students, Academics and the State - Frew, C. (Journal of University Teaching and Learning Practice, 2006)
Universities are no-longer isolated places where the intellectually or socially advantaged undertake research and contemplation. Universities are central to social and economic policy and can be used to meet the social and economic requirements of the new globalised environment. This paper explores the role of the internationalisation of universities in Australia, facing the challenge of globalisation, in light of declining government support of higher education institutions. A large part of internationalisation involves an increase in international student numbers, and this alongside changes in internal governance, is changing the role of academics within universities. This paper examines the new demands for an international educational literacy, examining the effect of these demands on academic professionals.